Reflexiones a partir de un abordaje psicoantropológico para los estudios de población - Martínez Salgado, Carolina (El Colegio de México A.C., 1994)
Socio-demographic research in the last decades has shown the need to develop transdisciplinary approaches to further understanding in this field. This paper discusses some of the posibilities that area opened to population studies by bringing in anthropological elements combined with others bases on socio-psychoanalysis. This proposal seeks to better understand the individual and family roots of population behavior as a specifically human phenomenon from a micro-social and qualitative perspective. The problem studied, as an empirical exercise is placed in the intersection o three very relevant aspects for population studies today: the biological reproduction, the relationship with the environment and the effect of both on health. The study encompasses both the individual and family levels. The text compares an urban area and a traditional town of the Xochimilco area in the south of Mexico City.